Analysis of regional economic development inequality: A case study of Belitung Island - Diti Artanti Utami Putri; Alifah Henir Robila; Nayla Aurelia Putri (Privietlab, 2026)
Economic inequality remains a persistent challenge in Indonesia’s regional dynamics, where aggregate growth does not automatically guarantee equitable development. This study examines spatial gaps, household expenditure variations, and intersectoral imbalances to assess economic equity on Belitung Island. Using a quantitative descriptive approach, the Williamson Index, Gini Index, and Shannon Entropy Index were calculated using secondary data from the Central Statistics Agency (BPS) for Belitung and East Belitung Regencies (2021–2025). The Williamson Index ranged from 0.084 to 0.105 with a downward trend, reflecting low interregional disparity. This aligns with the Shannon Entropy Index ranging from 0.748 - 0.770 for Belitung Regency and 0.809 - 0.829 for East Belitung Regency indicating a balanced sectoral structure. Similarly, Gini Index values (0.169–0.216 in Belitung; 0.196–0.218 in East Belitung) confirm evenly distributed household spending without extreme wealth concentration. However, contextualizing these macro-metrics with regional poverty indicators reveals a pattern of